Carbon capture and utilisation technologies: A systematic analysis of innovative applications and supercritical CO2 viability strategies - G.B. Silva Junior; J. Castro-Gomes; M. Magrinho (Journal of CO2 Utilization)
The growing increase in global carbon dioxide emissions is partially due to cement production, which has been an international concern. In this context, carbon capture and utilisation (CCU) technologies present themselves as a possible solution capable of using CO2 and other industrial waste and transforming them into value-added products.To explore the potential of this approach, this study conducted a systematic literature review of review articles published between 2018 and 2024, with the aim of systematising information on the materials, methods, and technologies associated with CCU in the construction sector. To this end, the properties and potential use as binders and/or aggregates of various materials were analysed. The available CCU technologies were compared, with particular attention given to supercritical carbonation, including a systematisation of innovative applications and feasibility strategies. In addition, the challenges associated with the implementation of these technologies were analysed.The results revealed a significant increase in publications on the subject in recent years. In addition, the potential of biocements was highlighted, particularly for the repair of cracks in concrete. Biochar and slag proved to be viable for use as aggregates or binders. The study also revealed the emerging potential of supercritical carbonation in comparison to accelerated carbonation, particularly due to its high CO2 capture efficiency. On the other hand, several challenges were identified, including a limited understanding of the reaction mechanisms.Finally, the study proposes a set of recommendations to support the implementation of the low-carbon strategies discussed, which have the potential to transform the construction sector.